Analisa Performa Mesin Diesel Dengan Variasi Pembebanan Di PT PLN UPLTD MG Nunukan - Andre Amba Matarru; Ferdinan Sanda (Politeknik Caltex Riau, 2022)
Electricity is now a primary need that is very important for everyday life, both for household use and in industry. Electricity supply should be spread evenly throughout Indonesia, therefore it is important to distribute electricity to Indonesia, especially the Nunukan area, North Kalimantan which until now is experiencing good development with the addition of diesel engine units that can help distribute electricity to the people of Nunukan. The purpose of this study was to determine the performance of the Mitsubishi engine with the S16R-PTA (-S) model. The method used was by conducting a literature study and taking data on the diesel engine and performing calculations so that the research that was carried out at the PLTD Sei Bilal obtained data to calculate the thermal efficiency and net work of a diesel engine. From the data obtained, calculations were made and concluded that at 600 kW power the highest thermal efficiency was 59.3% and at 800 kW and 1000 kW the highest net effort was 614.36 kJ/kg.